2013
DOI: 10.3109/03009734.2013.814734
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma glutamyl transferase and alanine transaminase concentrations predict endothelial dysfunction in patients with non-alcoholic steatohepatitis

Abstract: Purpose. Cardiovascular diseases are the leading cause of death in patients with non-alcoholic steatohepatitis (NASH). We aimed to investigate the presence of endothelial dysfunction and whether serum concentrations of liver enzymes may reflect the severity of such an endothelial dysfunction in patients with NASH.Methods. Fifty patients with NASH diagnosed by liver biopsies and 30 healthy controls were included. Blood samples after fasting were harvested for measurements of glucose, insulin, cholesterol, trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
(28 reference statements)
1
22
0
1
Order By: Relevance
“…Serum ALT levels have been positively associated with the risk of carotid atherosclerosis in patients with NAFLD, suggesting that serum ALT levels could be used as a surrogate marker for cardiovascular risk in a specific clinical setting 57 . In patients with non-alcoholic steatohepatitis (NASH), serum GGT and ALT concentrations might be predictors of CIMT 58 . Increased serum ALT levels (even levels at the high end of normal) are associated with markers of CVD 59 , and they may therefore have prognostic value in assessing NAFLD patients, in whom they may potentially indicate an increased risk of CVD[62].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ALT levels have been positively associated with the risk of carotid atherosclerosis in patients with NAFLD, suggesting that serum ALT levels could be used as a surrogate marker for cardiovascular risk in a specific clinical setting 57 . In patients with non-alcoholic steatohepatitis (NASH), serum GGT and ALT concentrations might be predictors of CIMT 58 . Increased serum ALT levels (even levels at the high end of normal) are associated with markers of CVD 59 , and they may therefore have prognostic value in assessing NAFLD patients, in whom they may potentially indicate an increased risk of CVD[62].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NAFLD [ 35 , 73 - 75 ] and AFLD [ 35 , 76 ] had significantly increased CIMT, and the association between NAFLD and subclinical atherosclerosis was independent of traditional risk factors [ 75 ]. ALD may also promote the premature increase in CIMT [ 76 ] via mechanisms that might include insulin resistance [ 77 ] and abnormal liver function, including ALT [ 78 , 79 ] and GGT [ 78 ], in patients with NAFLD and NASH. Age and metabolic factors are also associated with CIM thickening in patients with ALD.…”
Section: The Associations Between Cimt and Traditional CV Risk Factormentioning
confidence: 99%
“…However, coronary artery disease (CAD) variants were not found to be associated with CIMT and did not appear to mediate the risk of atherothrombosis through known risk factors [ 90 ]. Additionally, impaired FMD under various statuses and diseases might led to thicker CIM [ 78 , 92 , 93 ]. Their exact mechanism remains unknown and needs to be further studied.…”
Section: The Associations Between Cimt and Novel Risk Factorsmentioning
confidence: 99%
“…123,124 Furthermore, it has proposed that elevated circulating levels of ALT and AST are associated with endothelial dysfunction (carotid artery intima-media thickness and flow-mediated dilatation)-induced atherosclerosis and inflammation. 125 Data from the Framingham Heart Study have shown, after adjusting for confounding variables, over a 10-year follow-up period among 3744 white adults in the United States who were free from clinical HF at baseline, there was an increased risk of AF associated with increased serum, either marker ALT or AST (>40 U/L). 115,126 Thus, ALT and AST levels are independently associated with increased CVD-related mortality and serve as surrogate predictive markers in CVD progression.…”
Section: Alt and Astmentioning
confidence: 99%